Integration of Talking Stick and Audio Visual: an Innovative Approach in Improving Student Learning Outcomes - Sa'diyah, Halimatus; Manshur, Umar; Suhermanto, Suhermanto (UAS PRESS, 2024)
This article aims to explore and analyze the application of the Talking Stick learning model assisted by audiovisual media at Madrasah Tsanawiyah Misbahul Fata Banyuwanyar. The main focus of this article is to identify how to implement this learning model and evaluate its impact on student learning motivation and understanding of lesson material. The research method used is descriptive qualitative with a case study approach. Data was collected through in-depth interviews, observation, and documentation, then analyzed using data reduction techniques, data display, and drawing conclusions by data triangulation. The research results showed that the application of the audiovisual-assisted Talking Stick learning model succeeded in increasing students' active participation. By giving each student the opportunity to speak in turn, this method encourages greater engagement and attention to the lesson material, as well as enriching the learning experience through audiovisual aids. Student learning motivation has increased significantly, students have become more enthusiastic and dedicated to the learning process, thanks to interactive methods and the support of a positive learning environment. The dynamic and inclusive classroom atmosphere that is created provides an effective and enjoyable learning environment, where every student feels valued and encouraged to participate. It is hoped that these findings will provide new insight into the effectiveness of the Talking Stick learning model and provide practical recommendations for educators in adopting innovative learning methods to improve the quality of learning.